Level Up Your Front-End Skills with React JS - Saptrian, Muhammad Daffa; Ramadhan, Muhammad Thoriq; Syauqi, Muhammad Haikal; Adharani, Yana; Mujiastuti, Rully; Ambo, Sitti Nurbaya (Society : Jurnal Pengabdian Masyarakat, 2025)
A limited understanding of Front End Web Development remains a significant obstacle for many students and the general public, particularly in mastering modern frameworks like ReactJS. To address this issue, the community service team from the Informatics Engineering Study Program at the University of Muhammadiyah Jakarta organized a webinar and workshop titled â€œLevel Up Your Front-End Skills With React JSâ€ as part of their community service initiative. This activity combines an online approach to delivering material with hands-on practice to provide participants with a comprehensive understanding. The training material covers basic web development concepts, React JS component structure, state management, and implementing a simple mind mapping application. The effectiveness of the activity was evaluated through pre-tests, post-tests, and participant feedback surveys. The evaluation results showed a significant improvement in participants' understanding, with an average pre-test score of 79.5% increasing to 89.7% on the post-test. Additionally, feedback indicated positive responses to the quality of material delivery and the relevance of the content. This activity successfully expanded access to Front-End Web Development technology learning and contributed to developing digital talent adaptable to current industry needs.